Inheritance for Non-Muslim Children from the Perspective of the KHI (Study of Ruling No. 232¬/Pdt.P/2026/PA.Sby) - Farhan Haban Nugraha; Harmono (Indonesian Journal of Advanced Research, 2026)
The Compilation of Islamic Law (KHI) stipulates that both the decedent and the heirs must be Muslim; therefore, non-Muslim children generally have no right to inherit from Muslim parents. However, in the practice of religious courts, there has been a legal development through the granting of a mandatory bequest (wasiat wajibah) to non-Muslim children, as outlined in Ruling No. 232/Pdt.P/2026/PA. Sby. This study aims to analyze the inheritance provisions for non-Muslim children according to the KHI and to examine the implementation of the rights of children of a different religion in that ruling. This study employs a normative legal research method using both a statutory approach and a case-based approach. The legal materials utilized consist of primary, secondary, and tertiary sources. The findings indicate that Islamic inheritance law and the KHI do not recognize interfaith inheritance, as religious affinity is a primary requirement in inheritance relationships. However, through the development of Supreme Court jurisprudence, non-Muslim children can still receive a share of the estate through the mechanism of a mandatory bequest (wasiat wajibah) as a form of protection for a sense of justice and the welfare of the family. Nevertheless, this practice remains controversial because it is not explicitly regulated in the KHI. Therefore, legal reform is needed to provide legal certainty while addressing the need for justice in a diverse society.